2010
DOI: 10.1136/sti.2010.042861
|View full text |Cite
|
Sign up to set email alerts
|

A randomised controlled trial to assess pain with urethral swabs

Abstract: Direct urethral sampling is associated with discomfort and/or pain in men, which was significantly greater with a swab than a plastic loop. Urine should therefore be the specimen type of choice. When direct urethral sampling is indicated a loop is preferable to a urethral swab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…1,2 Either a 5 mm plastic loop or cotton tipped swab can be used, which should be introduced about 1 cm into the urethra. 38 (1b) Other methods are also used, including a sterile blunt curette or spatula. 39…”
Section: Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 Either a 5 mm plastic loop or cotton tipped swab can be used, which should be introduced about 1 cm into the urethra. 38 (1b) Other methods are also used, including a sterile blunt curette or spatula. 39…”
Section: Aetiologymentioning
confidence: 99%
“…4,[39][40][41] • If a urethral discharge is present the smear can be sampled without placing the device inside the meatus. 38…”
Section: (C)mentioning
confidence: 99%
“… 2 3 Taking urethral swabs for GSUS is uncomfortable for patients. 4 Furthermore, microscopy requires skilled personnel and possesses significant inter-user and intra-user variability, 5 6 variable sensitivity and low specificity for predicting infection. 7 Reduced use of microscopy for asymptomatic patients and the expansion of ‘test and treat’ community-based sexually transmitted infection screening programmes for Chlamydia trachomatis infection only reduce the potential for empirically treating other infective causes of NGU, such as Mycoplasma genitalium .…”
Section: Introductionmentioning
confidence: 99%
“…Meatal swabs are likely better tolerated than urethral swabs, as demonstrated in a comparison study of men who received both a urethral and meatal swab, which found that 76% of men preferred the meatal swab (4). Another study attempted to quantify, using a visual analogue pain scale, the discomfort associated with urethral swab collection and found that collection with a urethral swab using the standard technique (inserting a swab 2 cm into the distal urethra) elicited a median pain score of 52 mm (on a 100-mm pain scale), which correlated with moderate (Ͼ30 mm) to severe (Ͼ54 mm) pain (10). Furthermore, multiple studies have identified discomfort from urethral swabbing as a major factor that causes men to delay seeking health care (11)(12)(13), and participants in adolescent focus groups expressed strong negative emotions when asked about the urethral swab testing process (12,13).…”
Section: Discussionmentioning
confidence: 99%